Peningkatan Pengalaman Terhadap Pengguna Aplikasi Katalog Frame Kacamata Menggunakan Teknologi Augmented Reality - Muhammad Yudha Yusi Putra; Wibisono Sukmo Wardhono; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
At this time glasses is also called as Eye Wear which is glasses enhances the aesthetic of it's wearer and if the glasses that was bought from online shop wasn't as buyer expected because the buyer couldn't try it first surely it will decrease the buyer satisfaction , in turn they will be back to the old way of buying glasses which is directly go to the nearest optical glasses shop that is surely time and energy wasting, also the desired glasses model was not necessarily available. By utilizing the android smartphone with technology of augmented reality in glasses catalog, the buyer can directly interact with the desired glasses whenever and wherever they please which in turn will simplify the consumer in choosing the right glasses in real-time with the purpose of increasing the user experience at shopping and using the glasses catalog app. So the glasses catalog app was made with augmented reality technology using unity software and comparing the user experience with already deployed augmented reality-less app optik melawai using user experience questionnaire method with focused on hedonic quality aspect. The result which was found in the research was user experience that used the glasses catalog app with augmented technology was increased from value of 0,688 to 1,513 after the app was analyzed and tested by using user experience questionairre in hedonic in hedonic quality category.